2007
DOI: 10.1074/jbc.m609552200
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role for Polar Residues in Coupling Leukotriene B4 Binding to Signal Transduction in BLT1

Abstract: Seven transmembrane receptors widely known as G-proteincoupled receptors (GPCRs) 4 (1, 2) mediate an array of physiological processes in response to such diverse agonists as peptides, amino acid derivatives, and lipids. Despite the great diversity in their ligands, the conserved motifs found across this superfamily and the limited interacting partners such as G-proteins (3) and ␤-arrestins (4) at the cytoplasmic interface point toward a common activation mechanism for GPCRs. GPCRs constitute the single larges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 56 publications
6
34
0
Order By: Relevance
“…The EL2 has been suggested to be involved in the binding of diverse types of ligands, such as aminergic receptor ligands (Laurila et al, 2007;Scarselli et al, 2007), nicotinic acid (Tunaru et al, 2005), leukotriene B 4 (Basu et al, 2007), or vasopressin (Conner et al, 2007). The involvement of EL2 in the binding pocket of aminergic GPCRs has originally been suggested for the dopamine D 2 receptor on the basis of detailed substituted-cysteine accessibility analysis (Shi and Javitch, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The EL2 has been suggested to be involved in the binding of diverse types of ligands, such as aminergic receptor ligands (Laurila et al, 2007;Scarselli et al, 2007), nicotinic acid (Tunaru et al, 2005), leukotriene B 4 (Basu et al, 2007), or vasopressin (Conner et al, 2007). The involvement of EL2 in the binding pocket of aminergic GPCRs has originally been suggested for the dopamine D 2 receptor on the basis of detailed substituted-cysteine accessibility analysis (Shi and Javitch, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The binding site of cysteinyl leukotrienes to either of their receptors has not been determined. However, it has been shown that LTB 4 , a leukotriene lacking the cysteinyl moiety, uses, when binding to its high-affinity receptor (BLT1), residues in the C-terminal part of the ECL2 and TM5, regions possibly affected by the M201V mutation (Gearing et al, 2003;Sabirsh et al, 2006;Basu et al, 2007).…”
Section: Signaling By the M201v Mutant Of The Cyslt2 Receptor 435mentioning
confidence: 99%
“…Mutations of the TM1 residue Asn36, TM3 residue Asp64, and the TM7 residues Ser277, Ser278, Ser279 and Asn281 produced a significant reduction in L TB4 mediated chemotaxis and calcium mobilization. Specifically, mutation of these residues prevented interactions between Asp64 and Asn281 as well as Asp64 and Asn36, which were required for transition of the molecule to its active state [151]. Similar studies involving the thyrotropin receptor [340] and histamine H1 receptor [341] revealed that mutation of TM regions could prevent transition of the receptors to the active state.…”
Section: Chapter IV Validation Of Inhibitor Compounds Identified By Vmentioning
confidence: 82%
“…Some of the most common methods include assessment of CXCL 12-induced calcium mobilization [149][150][151], phosphorylation of secondary Signaling molecules such as ERK1/2, JNK, MAPK, and GSK 3a/~ [151][152][153], and internalization assays to assess the activity of ~-arrestin [142][143][144]. Assessment of CXCL 12-induced calcium mobilization involves pretreating cells with Fura-2 or Indo-I, fluorescent dyes which alter the ratio of their emissions in response to exposure to calcium.…”
Section: Cxcr4/cxcl 12 Signaling Occurs By a Variety Of Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation